Identification of peste des petits ruminants virus along with co-infecting diseases of goats in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Peste des petits ruminants (PPR) virus is the main infectious cause of goat mortality in Bangladesh, and co-infection may make diseases more severe. This study aimed to detect PPR and co-infecting diseases in goats. Materials and Methods: One hundred goats suspected to be infected with the PPR virus were collected from various areas of Mymensingh district, Bangladesh. A systemic post-mortem examination was carried out on PPR-suspected goats. Lungs, spleen, and lymph nodes (pre-scapular) were used for ribonucleic acid extraction, whereas lungs and mesenteric lymph nodes were used for deoxyribonucleic acid extraction. Seven-pair primer sets were used for molecular detection of pathogens specific for PPR, goat pox, contagious ecthyma (Orf), foot and mouth disease (FMD) virus, Klebsiella sp., and Mycobacterium sp. Reverse transcriptase-polymerase chain reaction (RT-PCR) or polymerase chain reaction (PCR) were used to find the exact cause. Results: Out of 100 PPR-suspected goats examined, 55 goats were confirmed as PPR-detected by RT-PCR. Among the 55 PPR-positive goats, 2 were co-infected with goat pox, 2 with tuberculosis, 10 with Klebsiella sp. infection, and 6 with FMD as detected by PCR and RT-PCR. Moreover, 12 goats were co-infected with PPRV and fascioliasis. Conclusion: About 58% of PPR virus-infected goats were co-infected with other organisms. There is a need to design technology to detect the state of co-infectivity at its early onset and future preventive and therapeutic strategies for co-infecting diseases. This is the first study in Bangladesh to describe co-infecting diseases of goats along with PPR.   J. Adv. Vet. Anim. Res., 9(3): 463–470, September 2022http://doi.org/10.5455/javar.2022.i615